Isolation, Characterization and Antimicrobial Activity of Imipramine-Cobalt (II) Complexes - Bhojya Naik, H.S.; Ramappa, P.G. (Asian Journal of Chemistry, 2010)
A series of seven new coordination compounds of Co(lI) with imipramine hydrochloride (lPH) has been isolated in non-aqueous media. The new complexes are characterized by thermal analysis, IR, electronic spectra, magnetic moments and conductivity measurements. The IR data suggest that IPH acts as a bidentate ligand. On the basis of spectral data, an octahedral structure is proposed. Thermogravimetric studies indicate the presence of water molecule in the complex. The molar conductance value shows the nonelectrolytic nature of the complexes. These complexes exhibit enhanced antimicrobial activity compared to that of free ligand .